The Uniqueness formation of Papuan Malay in Morphologically - Herlandri Eka Jayaputri; Dwiyanto Djoko Pranowo (Journal of English Language Teaching and Linguistics, 2018)
Indonesia has many Malay speakers and it spreads to Papua with the influence of Ambon and Indonesian becomes one of the variations in the Papuan Malay dialect. Papuan itself is the home of 275 languages that are 218 non-Austronesian or Papuan (79%) and 57 languages are Austronesian (21%) (Lewis et al. 2013 cited in Kludge, 2014). Moreover, the influence of Ambon and the North Moluccan Malay, and Indonesia played an important role especially in the formation of Papuan Malay (Paauw, 2008). Papuan Malay language is spoken by the inhabitants of the West Papua and uses as the daily language (Kludge, 2014). The formation of Papuan Malay has the uniqueness because it uses deletion some syllables but does not have the impact of the meaning. This study aims to know and explain the process of clipping word of Papuan Malay as well as their word classes. The Data come from the video of MOB Papua.  Besides that, the method used in this study is a Padan method with comparing other langue. Therefore, this study appears the history and role of Papuan Malay and compare the Indonesian with Papua Malay to find the clipping word process in Papuan Malay.